The Experiential Social Work Educator: Integrating Sociometry into the Classroom Environment. Issue 2 (15th March 2021) - Giacomucci, Scott; Skolnik, Sari
ABSTRACT: Social work education fully endorses experiential learning through its field placement component, while experiential teaching methods are only somewhat used in the classroom. This article outlines the utility of action-based mutual aid processes in teaching social work. Three experiential sociometric group tools are presented with their application in various social work education settings and at the beginning, middle, and ending stages of a course. Each of these sociometry processes – spectrograms, floor checks, and step-in sociometry, are depicted with their inherent capacity to cultivate mutual aid, bring the course content to life, and be adapted for any topic or classroom.